Employee Readiness for Artificial Intelligence Implementation in Companies: An Analysis of the Determinants of Successful AI AdoptionEmployee Readiness for Artificial Intelligence Implementation in Companies: An Analysis of the Determinants of Successful - Nasir Ismail; Harun Hassan; Muhammad Harith (IHSA Institute, 2026)
The rapid advancement of Artificial Intelligence (AI) has transformed organizational operations and accelerated digital transformation across various business functions, including human resource management, finance, manufacturing, marketing, customer service, logistics, and strategic decision-making. As organizations increasingly invest in AI technologies to improve productivity, operational efficiency, innovation, and competitiveness, employee readiness has emerged as a critical factor determining the success of AI implementation. This study aims to analyze employee readiness toward AI implementation in companies and identify the key factors influencing successful AI adoption. A quantitative research approach employing a cross-sectional survey design was adopted. Data were collected through structured questionnaires using a five-point Likert scale from 328 employees working in organizations that had implemented or were implementing AI technologies. Respondents were selected using purposive sampling, and the data were analyzed using descriptive statistics and Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings indicate that employees generally demonstrate a moderate to high level of readiness for AI implementation. AI knowledge, digital literacy, organizational support, AI training, leadership support, trust in AI, change readiness, perceived usefulness, and self-efficacy were found to have significant positive effects on employee readiness, whereas technology anxiety negatively influenced employees' willingness to adopt AI technologies. Among these factors, AI training and leadership support emerged as the strongest predictors of employee readiness. These findings contribute to the literature on AI adoption and organizational readiness while providing practical recommendations for organizations to strengthen AI literacy, employee development, leadership engagement, and human-centered AI implementation strategies to ensure sustainable digital transformation.